Exploring the Influence of Political Connections, Managerial Ownership, Capital Intensity and Company Size on Tax Aggressiveness - Sulistyana, Dewi; Ismanto, Juli (Lembaga Penelitian Universitas YARSI, 2025)
This study aims to identify the effect of political connections, managerial ownership, capital intensity, and company size on tax aggressiveness. The data used in this study are secondary, taken from the financial statements of companies listed in the energy sector index on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The analysis method used is panel data regression, with sampling using purposive sampling. From this process, nine companies were selected as research objects for five years. The results of the study indicate that political connections have a significant effect on tax aggressiveness. On the other hand, managerial ownership, capital intensity, and company size do not have the same effect. This finding indicates that companies with political connections tend to be more aggressive in managing their tax burdens. These political connections can provide certain access and benefits that allow companies to implement more aggressive tax avoidance strategies. The implications of tax aggressiveness found in this study are that companies need to ensure that their financial statements are prepared in accordance with Financial Accounting Standards and make wise decisions in terms of taxation, without taking aggressive actions in tax avoidance.